The Use of Rock Phosphate as a Source of Phosphorus on a slightly acid clayey Soil in Tanzania - Msaky, J.J.T.; Msanya, B.M.; Uriyo, A.P. (Afrika Focus, 1986)
The effectiveness of rock phosphate as a phosphorus nutrient source was studied as compared to triple superphosphate (TSP), a common fertilizer used in Tanzania. Initial results showed that rock phosphate can be used as a P source for growing maize. Its application increased both grain yields and soluble floride extractable P in the soil. TSP still proved to be superior to rock phosphate for the direct effect experiments in terms of both grain yield and soluble fluoride extractable P. However, for the residual effects experiment, rock phosphate was equally effective as TSP. Grinding rock phosphate beyond -40+60 mesh did not result in an increase in soluble P. However, increase in levels of application resulted into increased soluble P in soil. A combination of fineness and level of application resulted into an increased amount of soluble P. This combination should thus be used as a criterion in the use of rock phosphate as a P nutrient source for plant growth. KEYWORDS : Rock Phosphate, phosphorus source, soils, Tanzania